Information consulting : Guide to good practice - Wormell, Irene; Mikulas, Gabor; Olesen, Annie Joan.; ScienceDirect eBooks (Oxford [England] : Chandos Publishing (Oxford) Ltd, 2011)
This book presents a closer look at what makes information consultants successful and how they develop a productive relationship with their clients. While most of the books on this subject area are providing the experiences of information consulting veterans on 'how do you really do it?', the aim of this book is focused on exploring the nature of information management consulting. This incluses the task of the advice-and-guidance variety, such as helping clients to analyze and solve problems or to meet opportunities with the element of 'What should I do?'. The authors have used their extensive international and professional networks to take the challenge of letting the clients speak about their experiences and expectations in hiring information consultants.
What is information consulting? Advantages: why information consulting might appeal to you -- Challenges: realities to consider -- The starting point: Make a business plan -- The legal environment -- Building trust and marketing your services -- Client relations: The key to success -- Advice from other information consultants -- Take a leap from being a librarian to becoming an information consultant -- The clients speak: from a client's perspective -- Ahead.
Includes bibliographical references and index.
Elsevier
Safari Books Online
Keywords: Consulting firms -- Standards; Consulting firms -- Management; Knowledge management; Organizational effectiveness; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Consulting firms -- Management; Consulting firms -- Standards; Knowledge management; Organizational effectiveness; Electronic books